“Fatherman” On the Move: Social Transformation Strategy in Indonesian Family Education - Lestari, Lenni (Muslim Education Review, 2023)
“Fatherlessness” has long been a worldwide issue and social trend of our time. Research suggests that high-risk children in single-parent homes have nearly five times greater chance of developing mood disorders than those in co-parenting households. This article discusses “Fatherman”, an agency that voices the vital role of fathers in becoming psychological heroes for their children. The study aims to explore the strategy of the “Fatherman” agency in educating parents in Indonesia and to understand how “Fatherman”’s initiatives relate to gender roles and their broader impact on Indonesian society. This study employed a qualitative research approach by utilizing the content analysis method on several “Fatherman” social media accounts and books. The findings of this study revealed that the strategy adopted by the founders of the “Fatherman” account, namely Ustadz Bendri Jaisyurrahman and Ayah Irwan Rinaldi, makes fathers aware of their important role in the domestic sphere. This can be seen from the testimonials of online course participants, followers of the “Fatherman” account, and readers of the “Fatherman” books. Furthermore, the understanding of fatherhood has changed over time. Fatherhood has always been a multifaceted concept, from just being a provider (nafaqah) to becoming a role model for children, giving marital support, and nurturing. Based on a gender perspective, “Fatherman” still seems ambiguous and semi-patriarchal. The fundamental barrier is that masculinity, as currently constructed, becomes a tension for men to be fully involved in nurturing and household work. While “Fatherman” aims to encourage fathers to actively engage in parenting, they advertently reinforce gender superiority or perpetuate traditional gender roles. The social transformation that “Fatherman” offers is a changing perception of a father’s role in nurturing. Certainly, there is no “one-size-fits-all” solution to the fatherlessness crisis in Indonesia today. However, “Fatherman” agency will be one of the leading voices in providing an understanding of the father’s role.